Meta-analysis on the risk of fatal adverse events by bevacizumab, cetuximab, and panitumumab in 31 randomized trials including 25, 000 patients with colorectal carcinoma. Issue 25 (19th June 2020) - Chen, Jianxin; Wang, Junhui; Ni, Tao; He, Huijuan; Zheng, Qinhong
Abstract: Background: Targeted drugs including bevacizumab, cetuximab, and panitumumab have been widely used during the management of patients diagnosed with colorectal carcinoma, especially as palliative treatment. The present meta-analysis was performed to evaluate the fatal adverse events (FAEs) of targeted drugs including bevacizumab, cetuximab, and panitumumab in patients with colorectal cancer. Patients and methods: Studies of prospective, randomized, and controlled feature from EMBASE, Medline, and Cochrane Library, which reported FAEs potentially associated with bevacizumab, cetuximab, and panitumumab were adopted. Clinical characteristics and FAEs were collected from the enrolled literatures, with the quality of which been evaluated. Pooled analysis of FAEs, caused by each agent as first line, second/further line, and adjuvant treatment were performed with relative risks (RRs) and their corresponding 95% confidence intervals (CIs) in software RevMan 5.3. Results: Thirty-one studies including 25, 939 patients were brought into the final analysis. The RR and its 95% CI of the FAEs among all the agents including bevacizumab, cetuximab, and panitumumab was 1.07 (95% CI, 0.89–1.29; P = .50). The RRs and their 95% CIs of the FAEs as first line, second or further line, and adjuvant treatment related to bevacizumab were 0.91 (95% CI, 0.62–1.32; P = .61), 1.14 (95% CI, 0.57–2.28; P = .71), and 1.10 (95% CI, 0.67–1.79; P = .72). The RRs and their 95% CIs of the FAEs as first line, second or further line, and adjuvant treatment related to cetuximab were 1.02 (95% CI, 0.60–1.76; P = .93), 2.51 (95% CI, 0.49–12.88; P = .27), and 2.40 (95% CI, 1.00–5.77; P = .05). The RRs and their 95% CIs of the FAEs as first line, second or further line treatment related to panitumumab were 1.40 (95% CI, 0.89–2.18; P = .14) and 0.68 (95% CI, 0.43–1.09; P = .11), respectively. Conclusions: The present meta-analysis did not show any significantly increased RR of FAEs belonging to bevacizumab, cetuximab, or panitumumab, whether as first line, second/further line, or adjuvant treatment among patients with colorectal carcinoma comparing to placebo or blank treatment.